Polemik Akal dan Wahyu dalam Lanskap Pemikiran Islam (Antara Rasionalisme vis a vis Fideisme) - Sabara Sabara (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2015)
This thesis talks about epistemology case belongs to the usage of ratio and revelation in religion knowledge and polemic of the both otority in an History of Islamic Thought. Ratio is a faculty of epistemology that has relation with knowledge that can be reached by all people, there is no exception, in fact revelation is a spesiefic knowledge given by Faithfully Allah to His follower that exhibited in to Alquran. The motion about ratio and revelation in history of Islamic thought, is an eternal motion therefore it has appeared some various of thought and school in some thought of islam, they are aqidah, fiqih, and also sufism. Generally, the polemic between ratio and revelation in history of islamic thought appears two tendentions that opposite each other, they are rasionalism versus fideism. Rasionalism believes that mind has got otority in religion cases, the opposite fideism denies the role of mind in religion cases. The two of thought varieties, shown in some kinds of Islamic schools, not only sunni, but Syiah also.